Heavy metal biosorption from aqueous solutions by algae inhabiting rice paddies in Vietnam. Issue 2 (June 2016) - Tran, Hang Thi; Vu, Ngo Dinh; Matsukawa, Masahito; Okajima, Maiko; Kaneko, Tatsuo; Ohki, Kaori; Yoshikawa, Shinya
Abstract: The gelatinous colonies collected from rice fields in Phu Tho Province, Viet Nam (Al-VN) were investigated to remove heavy metal ions from water for the first time. The biosorption of Cu 2+, Cd 2+ and Pb 2+ by dried Al-VN was tested at various pHs, temperatures, contact times, biosorbent doses and initial metal ion concentrations under laboratory conditions. Metal ion adsorptions on Al-VN were strongly dependent on pH, with the optimum pH for adsorption of Cu 2+, Cd 2+ and Pb 2+ solutions being 4, 5–7 and 5–6, respectively. The biosorption capacity of metal ions by Al-VN was independent of temperature. After one hour of contact time, the adsorption capacity reached equilibrium. The maximum adsorption capacity (qm ) of Cu 2+, Cd 2+ and Pb 2+ was 27.78, 28.57 and 76.92 mg/g, respectively. Both the Langmuir and Freundlich adsorption models were suitable for biosorption of Cu 2+, Cd 2+ and Pb 2+ by Al-VN. The desorption studies indicated that 0.1 M HNO3 was an efficient desorbent for recovery of Cu 2+, Cd 2+ and Pb 2+, and the maximum desorption was >90%. These results indicate that Al-VN can be used as an efficient and economic biosorbent for the removal and recovery of toxic heavy metal ions from polluted water.